The social history of the Dar Al-Dhikr Islamic community in Barangay Mansilingan, Bacolod City. - Crauz, John Niño Vinson
This is a study about the social life (religious and social, political and economic structures and features) of the Dar Al-Dhikr Islamic Community in Barangay Mansilingan, Bacolod City. Interview schedules with key informants and interviewees were conducted to determine the factors and processes that led to the establishment of the Dar Al-Dhikr Islamic Center; To identify the problems the Muslims of the Center have encountered and how they handled it; To discuss the socio-cultural adaptations of the Muslim members; and to assess the nature and extent of their integration and participation with the non-Muslim community. From this point, the description of the social life of the Dar Al-Dhikr Islamic Center, as another objective, was made possible., This research found out that a Muslim convert couple spearheaded the establishment of the Dar Al-Dhikr Islamic Center with the support of some pioneer members who majority were also converts. Since the Islamic Community is situated in a predominantly Christian barangay, it was hard for the non-Muslim to accept the existence of the Muslim community. The negative stereotyping and generalizations of the Muslims as terrorists and drug pushers were problems encountered by the Muslims. As a result, the Islamic Community experienced the negative views and reactions of the non-Muslims against them including the inspection of the Center by the military. To solve these problems, the Muslims tried to befriend the Christian community in view of propagating Islam. They also opened the Islamic Center to the curious public. Aside from that, there were also problems and conflicts among them as group, including financial problems. with regards to these, Islamic teachings and principles were their own solutions, plus the support (financial and spiritual) of the members. In terms of adaptation, it is not that striking compared to other Muslim minorities in the country. Since majority of the members are Negrenses, speaking HilIgaynon was not a problem. Though, Maranao and Tausug members have already adapted Hiligaynon. Some male members married local (Christian) women and some converted own family to Islam. These have been helpful in propagating the Islamic religion and for Christian's acceptance. The Islamic Community has been integrating with the projects and programs of the city government as well as with sectors and some militant organizations in the province. However, their relation with the latter is decreasing because of the political crisis in the country. The Muslims do not participate with purely religion-related activities. All in all, the social life of the Islamic Community is grounded on the teachings and principles of Islam. They live in an Islamic way from the aspects of religious and socio-cultural (e.g. prayers, beliefs, festivals, etc.), political (e.g. laws), and economic.